Measuring structure and interactions in colloidal fluids using test-particle insertion - Stones, AE (2020)
We use the Potential Distribution Theorem to evaluate distribution functions from equilibrium configurations using test-particle insertion. We use this methodology to determine the contact value of the pair distribution function in hard-disk systems: in contrast with the conventional distance-histogram method, the insertion measurement is exact and does not require an approximate extrapolation. The resulting equations of state in both simulations and a hard-disk colloidal model system agree well with the predictions of Scaled Particle Theory. We also provide the first experimental measurement of the cavity distribution function y(2)(r) inside the hard core.